Práticas integrativas e complementares em saúde na estratégia de saúde da família: perspectiva da odontologia - Alvarenga, Ana Claudia Cordeiro (2023)
Global interest in alternative and complementary medicine in healthcare is on the rise. In Brazil, such approaches are called Integrative and Complementary Health Practices, focused on stimulating the natural processes of health promotion, prevention, and recovery, with effectiveness and safety, valuing welcoming listening, establishing a therapeutic bond and integration of the individual with the environment and society. The institutionalization of the National Policy on Integrative and Complementary Practices in 2006, and the Municipal Policy on Integrative and Complementary Practices in Health of Vitória, Espirito Santo, in 2016, marks significant progress in the inclusion of unconventional therapeutic methods in the System Unified Health System. Although Integrative and Complementary Health Practices are formally integrated into the health network, their implementation dynamics remain little explored at the municipal level, especially in the Family Health Strategy and from the perspective of dentistry, representing a new and relevant field of study. Objective: Thus, we sought to understand how the perception of dental surgeons who work in the Family Health Strategy and managers of the technical area of Oral Health in the city of Vitória is constituted regarding the incorporation and implementation of Integrative and Complementary Practices in Health, from the perspective of disease prevention, health promotion and recovery. Methods: This is an exploratory, descriptive study, with a qualitative approach. The sample was constituted by saturation. Semi-structured interviews were used with forty dental surgeons and two managers, recorded, transcribed, and subjected to Bardin's content analysis. Results: Three categories emerged from the results: understanding of Integrative and Complementary Health Practices; perception about incorporation and implementation of Integrative and Complementary Health Practices; and perception about Integrative and Complementary Health Practices policies. Regarding dental surgeons, it was observed that there was unanimous understanding, acceptance, and interest in the practices, highlighting their value in line with the guidelines of related policies, highlighting the potential available in the municipality. However, challenges such as gaps in knowledge of specific dental policies and regulations, in addition to failures in continuing education, highlight the pressing need to improve dissemination and training strategies for professionals. In relation to managers, it was clarified that Integrative and Complementary Health Practices are valued for their holistic reach and potential at different levels of care. Despite the challenges, such as restricted dissemination, training and financing, and the predominance of the biomedical model, the incorporation and implementation of these practices stood out due to the commitment of managers in line with national and municipal policies, highlighting, however, the need to direct the provision of Integrative and Complementary Health Practices also for specific contexts such as dentistry. Conclusions: It is concluded that the municipality of Vitoria has great potential for expansion regarding the incorporation and implementation of Integrative and Complementary Health Practices in the Family Health Strategy from the perspective of dentistry, however, there is a need to recognize and remedy the obstacles that arise, in order to achieve its full potential. potential for the benefit of users, dentistry, the System Unified Health System and Brazil.